Decreasing Incidence of Postoperative Ileus following Total Knee Arthroplasty: A 17-Year Retrospective Review of 38,007 Knee Replacements at One Institution - Nguyen, Bob H.; Bono, Olivia J.; Bono, James V. (The Journal of Knee Surgery, 2020)
Ileus following total knee arthroplasty is a clinically and financially significant postoperative complication that has not been extensively described in the orthopaedic joint literature. Ileus has been found to occur in 0.7 to 4.0% of patients after total joint arthroplasty. In a 17-year period (2001 fiscal year through 2017 fiscal year) at one institution, we found an incidence of 0.500% (190/38,007) following knee arthroplasty. In addition, the incidence of ileus following total knee arthroplasty (TKA) has drastically declined over this 17-year period, from 1.593% (13/816) in 2001 to 0.120% (4/3,332) in 2017. This decrease may be attributed to a reduction in narcotic use postoperatively, earlier ambulation following surgery, and reduction in length of hospital stay. Though postoperative ileus is not yet a preventable complication, recognition of risk factors may permit earlier intervention to ameliorate some of the morbidity associated with this condition.
Keywords: ileus; postoperative ileus; total knee arthroplasty; orthopaedic surgical complications